A STORY OF DEBT AND BROKEN PROMISES? THE recruitment of guatemalan MIGRANT workers IN QUEBEC - Gesualdi-Fecteau, Dalia; Thibault, Andréanne; Schivone, Nan; Dufour, Caroline; Gouin, Sarah; Monjean, Nina; Moses, Éloïse (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2017)
For the past two decades, the number of immigrants admitted to Canada has remained relatively stable while the number of workers admitted with a temporary work permit has steadily increased. This phenomenon is explained by a shift in Canadian public policies that direct the management of labour migration. Recent research has shed light on the complex and highly ramified transnational network that allows the recruitment of temporary foreign workers. Agricultural Guatemalan workers are hired through the Temporary Foreign Worker Program and the recruitment process is controlled by private recruitment intermediaries. Some abusive recruitment practices have been consistently reported. This article seeks to present the results of an empirical study documenting the recruitment by Quebec employers of Guatemalan agricultural workers and will discuss the normative framework regulating the recruitment of Guatemalan temporary foreign workers.